Primary-school-aged children inspire their peers and families to eat more vegetables in the KiiDSAY project: a qualitative descriptive study - Karpouzis F.; Walsh A.; Shah S.; Ball K.; Lindberg R. (BMC, 2024)
Abstract Background While vegetable intakes in Australia remain sub-optimal across all age groups, children are rarely consulted about their ideas on how to increase consumption. Qualitative research involving children provides an opportunity to consider their views. The aim of the Kids initiative inspires Dietary Success in Adults and Youth (KiiDSAY) project was to explore the views of school-aged children, who had participated in a school-based nutrition education program, about inspiring their peers and families to eat more vegetables. Methods A total of 26 children (15 boys) aged 10-12 years from four primary schools in New South Wales, Australia, participated in seven focus group interviews. Purposeful sampling was used to recruit participants. The study involved open-ended semi-structured questions conducted via Zoom that were audio-recorded, transcribed verbatim and analysed using thematic analysis with deductive and inductive coding in NVivo. Results Four major themes emerged: (i) taste; (ii) family environment; (iii) healthy eating; and (iv) change makers; with subthemes that were embedded within Social Cognitive Theory and Ecological Model of Health Behaviour theoretical frameworks. Conclusions Children's inputs hold great potential for informing future interventions, particularly when designing or refining school-based nutrition programs. Children offered suggestions on how to inspire increased vegetable consumption among their peers and families that could be taken into consideration for future research and practice. These included: cooking activities in the home and school settings using recipes that creatively hide/mask/enhance the flavour of vegetables, involving positive role models and supportive school environments. Additionally, children recommended a sequential approach to the delivery of recipes starting from fruit-based and transitioning to vegetable-based recipes. Given the challenges faced in increasing children's vegetable consumption, particular focus on future research in this area is warranted. Trial registration FEAST Trial registered 14th December 2020 with the Australian and New Zealand Clinical Trials Registry (ACTRN12620001347954).